2012
DOI: 10.1159/000345221
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension as a Prognostic Indicator at the Initial Evaluation in Idiopathic Pulmonary Fibrosis

Abstract: Background: The impact of pulmonary hypertension (PH) on survival has been demonstrated in severe cases with idiopathic pulmonary fibrosis (IPF) who were referred for transplantation. However, whether PH is a predictor of survival remains unclear in milder cases. Objectives: To evaluate the survival impact of pulmonary artery pressure measured during the initial evaluation in patients with IPF. Methods: We retrospectively analyzed the initial evaluation data of 101 consecutive IPF patients undergoing right hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
202
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(218 citation statements)
references
References 37 publications
7
202
2
7
Order By: Relevance
“…Our study showed that 35% of IPF patients had high TRGP and demonstrated that TRPG was an independent prognostic factor for disease and patient outcomes. A previous study conducted to support the validity of our results was reported by Kimura et al 18 Under the evaluation of 101 mild IPF patients (mean %FVC 70.2±20.1%) undergoing RHC, they showed that 35% of the patients had a mean pulmonary artery pressure (m-PAP)>20 mmHg and suggested that m-PAP is an independent prognostic factor. PH is considered to be present even in mild stages in IPF patients.…”
Section: Pulmonary Research and Respiratory Medicinesupporting
confidence: 88%
“…Our study showed that 35% of IPF patients had high TRGP and demonstrated that TRPG was an independent prognostic factor for disease and patient outcomes. A previous study conducted to support the validity of our results was reported by Kimura et al 18 Under the evaluation of 101 mild IPF patients (mean %FVC 70.2±20.1%) undergoing RHC, they showed that 35% of the patients had a mean pulmonary artery pressure (m-PAP)>20 mmHg and suggested that m-PAP is an independent prognostic factor. PH is considered to be present even in mild stages in IPF patients.…”
Section: Pulmonary Research and Respiratory Medicinesupporting
confidence: 88%
“…In general, the prevalence of PH was similar in studies from Europe [18,25,[40][41][42][43][44][45][47][48][49], North America [5,6,26,28,46,[50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], Asia and Africa [37,[68][69][70][71][72][73][74][75], although the majority of evidence was reported from North America (n=23, 53%). Across studies, the prevalence of PH among IPF patients ranged from 3% to 86%; most estimates tended to be between 30% and 50% (figure 3) [25, 43, 44, 47, 50, 52-66, 68, 71-73].…”
Section: Pulmonary Hypertensionmentioning
confidence: 84%
“…A Kaplan-Meier curve revealed significantly worse survival among patients whose mPAP was >20 mmHg than among those whose mPAP was ⩽20 mmHg (log-rank test p=0.001). The median survival estimates were 20.8 and 37.5 months, respectively [74].…”
Section: Pulmonary Hypertensionmentioning
confidence: 98%
See 1 more Smart Citation
“…PATEL et al [16] observed that PH (mean PAP .25 mmHg) was an independent predictor of mortality in 376 patients with IPF referred for lung transplantation. In a recent study, KIMURA et al [32] confirmed by multivariate analysis that a high mean PAP value measured at the initial evaluation of IPF patients undergoing RHC is an independent predictor of survival. Unlike many other studies [1,33,34], this retrospective analysis focused on IPF patients affected by milder disease (mean FVC 70.2%, and mean DLCO 47.9%) [32].…”
Section: Prognostic Significance Of Ph In Ipfmentioning
confidence: 89%